Model pembelajaran Pendidikan Kewarganegaraan untuk Membangun Kompetensi Warga Negara - -, Samsuri (Jurnal Civicus, 2010)
Model pembelajaran Pendidikan Kewarganegaraan untuk Membangun Kompetensi Warga Negara